Characterization of microcystin-induced apoptosis in HepG2 hepatoma cells. (15th January 2020) - Krishnan, Anjali; Koski, Gary; Mou, Xiaozhen
Abstract: Microcystins (MCs) are a class of hepatotoxins that are commonly produced by freshwater cyanobacteria. MCs harm liver cells through inhibiting protein phosphatases 1 and 2A (PP1 and PP2A) and can produce dualistic effects, i.e., cell death and uncontrolled cellular proliferation. The induction of programmed cell death, i.e., apoptosis, in MC treated hepatic cells has been described previously; however, its exact pathway remains unclear. To address this, HepG2 human hepatoma cells were exposed to MC-LR, the most prevalent isomer of MCs, and morphological and physiological responses were examined. Microscopy and Alamar Blue assay showed that HepG2 cells responded to MC-LR treatment with apoptosis characteristics, such as clumping and shrinking of cells and detachment from the monolayer culture surface. A fluorescent caspase activation assay further revealed activation of all tested apoptosis-dependent caspases (i.e., caspase-3/7, 8 and 9) after 24 h of MC-LR treatment. Furthermore, caspase-8 was found being activated 4 h after MC-LR treatment, earlier than observed activation of caspase-9 (8 h after MC-LR treatment). These data demonstrated that MC-LR can induce apoptosis of HepG2 cells through both extrinsic and intrinsic pathways and that the extrinsic pathway may be activated before the intrinsic pathway. This indicates that extrinsic pathway is more sensitive than intrinsic pathway in MC induced apoptosis. This knowledge contributes to a better understanding of MC hepatotoxicity and can be further used for developing treatments for MC exposed hepatic cells. Highlights: Microcystins can induce liver cell apoptosis. Microcystin can induce expression of intrinsic (caspase 9) and extrinsic (caspase 8) -specific caspases in liver cells. Caspase 8 activated ahead of caspase 9 during microcystin-induced liver cell apoptosis.